Duodenal reflux during insulin-stimulated secretion. Issue 11 (November 1974) - Faber, R. G.; Russell, R. C. G.; Royston, C. M. S.; Whitfield, P.; Hobsley, M.
Abstract : Insulin-stimulated secretion has been studied in 67 subjects with intact vagi. The relationship between the changes in the concentrations of hydrogen and sodium ions in individual 10-minute samples showed a highly significant negative correlation. In quantitative terms, this correlation could be explained by the mixing of isotonic gastric juice and duodenal reflux but not by back-diffusion. In 37 subjects duodenal juice was labelled with either bromsulphalein (BSP) or indocyanine green (ICG), both dyes being excreted only in the bile. In aspirated gastric juice there were highly significant positive correlations between the concentration of the dye and the concentration of duodenal reflux calculated from a formula based on the output of sodium ions. The volume of duodenal reflux occurring during insulin-stimulated secretion was estimated from the sodium output in normal controls, in preoperative patients with duodenal ulcer, and in patients following vagotomy with or without a drainage procedure. Reflux following gastrojejunostomy greatly exceeded that occurring in all other groups. Reflux following vagotomy with no drainage procedure was less than that in preoperative patients, and in patients in whom pyloroplasty or gastrojejunostomy had been performed.